2022
DOI: 10.1038/s41467-022-29466-3
|View full text |Cite
|
Sign up to set email alerts
|

Photo-induced trifunctionalization of bromostyrenes via remote radical migration reactions of tetracoordinate boron species

Abstract: Tetracoordinate boron species have emerged as radical precursors via deboronation by photo-induced single electron transfer (SET) pathway. These reactions usually produce an alkyl radical and boron-bound species, and the valuable boron species are always discarded as a by-product. Given the importance of boron species, it will be very attractive if the two parts could be incorporated into the eventual products. Herein we report a photo-catalyzed strategy in which in situ generated tetracoordinated boron specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Based on the results of control experiments, and also according to our DBP strategy and previous reports, 11,12 we proposed a cascade pathway involving borylation via 1,4-metallate shift and B–N elimination steps through an alkenylboronate intermediate E , as shown in Scheme 3. One of the Bpin moieties of B 2 pin 2 is attacked by MeO–, which is generated in situ from the base and MeOH to provide adduct A , and subsequently, the alkoxy exchange between A and reactant 1 could form borate B .…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Based on the results of control experiments, and also according to our DBP strategy and previous reports, 11,12 we proposed a cascade pathway involving borylation via 1,4-metallate shift and B–N elimination steps through an alkenylboronate intermediate E , as shown in Scheme 3. One of the Bpin moieties of B 2 pin 2 is attacked by MeO–, which is generated in situ from the base and MeOH to provide adduct A , and subsequently, the alkoxy exchange between A and reactant 1 could form borate B .…”
mentioning
confidence: 74%
“…Inspired by our previous experience 11,12 on the domino-borylation–protodeboronation (DBP) strategy and long distance 1,4-metallate shift, base-promoted B–B bond activation and C–B bond formation, 13–15 we envisage that tetrasubstituted alkenylboronates might be constructed from propargyl amines by a subsequent borylation/B–N elimination reaction, and if successful, it will represent a novel B–N elimination process (Fig. 1D).…”
mentioning
confidence: 99%
“…In this case, the arylboronate is formed on the less hindered primary boronic ester, but, after radical generation, a boryl rearrangement occurs, affording the more stable secondary radical for subsequent reactivity. Recently, organolithium‐derived organoborates have also seen utility in photoredox‐catalysed protodeboronation [42] and styrene carbofunctionalisation protocols [43] . While these boronates are typically formed in situ under stringently dry conditions, it is believed the enhancement of redox properties will lead to new synthetic endeavors and future discoveries.…”
Section: Photocatalytic Activation Of the C−b Bondmentioning
confidence: 99%
“…Recently, organolithium-derived organoborates have also seen utility in photoredox-catalysed protodeboronation [42] and styrene carbofunctionalisation protocols. [43] While these boronates are typically formed in situ under stringently dry conditions, it is believed the enhancement of redox proper- ties will lead to new synthetic endeavors and future discoveries.…”
Section: Photoredox Activation Of Preformed Tetracoordinated Boratesmentioning
confidence: 99%
“…Stahl et al showed that electrochemical oxidation of NaOH–APE complexes provide access to benzylic radicals, and the Aggarwal group as well as our group, used phenyl lithium for the in situ preparation of alkylarylboronate complexes, which serve as alkyl radical precursors by single electron oxidation. As an alternative to the APE complex formation approach, the Renaud group reported a transesterification strategy for the in situ conversion of APEs into alkylboronic catechol esters (RBcat) . The RBcat compounds are more reactive radical precursors and undergo nucleohomolytic substitution by reaction with sulfonyl radicals, aryloxy radicals, or TEMPO to generate the corresponding alkyl radicals. However, alkylboronic catechol esters are far less stable than APEs and not easy to handle.…”
mentioning
confidence: 99%